Pengaruh Meme Marketing Dan E – Word Of Mouth Terhadap Keputusan Pembelian Di Marketplace Shopee - Farhan Khairudin; Ahmad Johan; Dedi Junaedi (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to analyze the influence of Meme Marketing and Electronic Word of Mouth on Purchase Decisions among Shopee marketplace users. The background of this research is based on the rapid development of digital marketing, which increasingly utilizes creative meme-based content and electronic consumer communication as tools to influence purchasing behavior. This study employed a quantitative method with descriptive and verificative approaches. The population consisted of Generation Z users of the Shopee marketplace in Bandung City, with a sample of 200 respondents selected using a non-probability sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The results showed that the mean score of Meme Marketing was 3.88, Electronic Word of Mouth was 4.16, and Purchase Decision was 4.13, all of which were categorized as high. Hypothesis testing revealed that Meme Marketing has a positive and significant effect on Purchase Decisions, Electronic Word of Mouth has a positive and significant effect on Purchase Decisions, and both Meme Marketing and Electronic Word of Mouth simultaneously have a positive and significant effect on Purchase Decisions. The coefficient of determination value of 0.600 indicates that the two independent variables explain 60% of the variation in Purchase Decisions, while the remaining 40% is influenced by other factors outside the scope of this study. The findings imply that optimizing meme marketing strategies and managing electronic word of mouth effectively can enhance consumer purchase decisions on the Shopee marketplace.